2022
DOI: 10.1021/acsabm.2c00573
|View full text |Cite
|
Sign up to set email alerts
|

Human ACE2 Peptide-Attached Plasmonic-Magnetic Heterostructure for Magnetic Separation, Surface Enhanced Raman Spectroscopy Identification, and Inhibition of Different Variants of SARS-CoV-2 Infections

Abstract: The emergence of Alpha, Beta, Gamma, Delta, and Omicron variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for several million deaths up to now. Because of the huge amount of vaccine escape mutations in the spike (S) protein for different variants, the design of material for combating SARS-CoV-2 is very important for our society. Herein, we report on the design of a human angiotensin converting enzyme 2 (ACE2) peptide-conjugated plasmonicmagnetic heterostructure, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…In the fields of nanotechnology and materials science, organic/inorganic hybrids are regarded as some of the most important materials of the 21st century. Many recent studies have explored the combination of metal nanoparticles with other organic/inorganic nanomaterials to improve SERS signals. , Common materials can be classified accordingly to form into sphere-like materials such as SiO 2 and Fe 2 O 3 , thread-like materials such as carbon nanotubes (CNTs) and polyvinyl alcohol (PVA) nanofibers, and sheet-like materials such as nanoclays and graphene . The use of nanohybrids increases the dispersibility of nanoparticles, as well as the electric field strength between metal particles.…”
Section: Introductionmentioning
confidence: 99%
“…In the fields of nanotechnology and materials science, organic/inorganic hybrids are regarded as some of the most important materials of the 21st century. Many recent studies have explored the combination of metal nanoparticles with other organic/inorganic nanomaterials to improve SERS signals. , Common materials can be classified accordingly to form into sphere-like materials such as SiO 2 and Fe 2 O 3 , thread-like materials such as carbon nanotubes (CNTs) and polyvinyl alcohol (PVA) nanofibers, and sheet-like materials such as nanoclays and graphene . The use of nanohybrids increases the dispersibility of nanoparticles, as well as the electric field strength between metal particles.…”
Section: Introductionmentioning
confidence: 99%
“…The recent coronavirus disease (COVID-19) outbreak caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected over 630 million individuals and has resulted in the death of over 6.6 million people as of November 2022, according to the World Health Organization (WHO) . While a great deal of effort has gone into developing new ways to treat and prevent the onset of COVID-19, it is still affecting many people around the world, and it appears that it will continue to be present for the foreseeable future …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such a change in ACE2 binding affinity due to mutations in the RBD amino acid sequence of S-protein makes ACE2-based capture detection advantageous for identifying SARS-CoV-2 variants . Though there are several reports on ACE2-based SERS sensors, , none of them take advantage of this. For example, Yang et al used ACE2-modified Au nanospike arrays and demonstrated a low limit of detection (LOD) of 80 copies/mL for SARS-CoV-2 in contaminated wastewater within 5 min .…”
mentioning
confidence: 99%
“… 16 Zhang et al used ACE2-modified AgNR substrates to test the availability of COVID-19 from 23 water samples against bacteria. 17 Li et al 18 and Pramanik et al 19 used Fe 3 O 4 -based SERS substrates to collect and concentrate SARS-CoV-2 for SERS detection. Awada et al 20 and Yeh et al 21 recently focused on S-protein detection and achieved LODs of 1 fM and 1 fg/mL, respectively.…”
mentioning
confidence: 99%